Cue Utilization and Skill Acquisition for a Line of Sight UAV. (September 2014) - Davies, Joel; Wiggins, Mark W.
This study was designed to establish whether a composite measure of driving-related cue utilization would predict learning performance in a line of sight Unmanned Aerial Vehicle (UAV) simulator. The participants comprised 50 first year university students, all of whom were current drivers and lacked any prior UAV experience. Participants initially completed the driving version of the EXPERT Intensive Skills Evaluation (EXPERTise) to assess their level of cue utilization. They then engaged in two, 15 minute training blocks during which they were asked to practice respectively the take-off and landing phases of operation a UAV simulator. The number of trials to reach criterion (three successful trials in succession) and the proportion of successful trials within the 15 minute blocks comprised the dependent variables. The results indicated that cue utilization four measures of UAV skill acquisition. The implications of the study are discussed in the context of training and selection for line of sight UAV operators in the future.